Virtual Machine Tool - Altintas, Y.; Brecher, C.; Weck, M.; Witt, S. (CIRP annals, 2005)
This paper presents current state of Virtual Machine Tool Technology and related ongoing research challenges. The structural analysis of machine tools using Finite Element models and their experimental calibration techniques are presented. The kinematic analysis and optimisation of machine tool elements are discussed with sample examples. The interaction between the control of the feed drives, cutting conditions and machine tool structure is presented. Multi-body dynamic models of the machine, which allow integrated simulation of machine kinematics, structural dynamics and control techniques, are discussed. The interaction between the machine tool, controller and cutting process disturbances are discussed with sample examples. The simulation of machining operation and its impact on the dynamics of the machine tool and CNC are elaborated. The paper presents both the summary of current and past research, as well as research challenges in order to realise a fully digitised model of the machine tool.